Individual Characteristics and Auditors’ Whistleblowing Intentions in Indonesia: The Selective Moderating Role of Group Cohesion - Ilham Maulana Saud; Siti Fatimah Az-Zahro; Hafiez Sofyani (Jurnal Ilmiah Akuntansi, 2026)
This study examines how individual characteristics influence auditors’ internal and external whistleblowing intentions and whether group cohesion moderates these relationships. It also investigates the relationship between team norms and group cohesion. Data were collected from 399 external auditors employed by public accounting firms in Jakarta, Tangerang, Bandung, Yogyakarta, and Semarang and analyzed using partial least squares structural equation modeling. The results show that desired moral approval, attitude toward whistleblowing, perceived behavioral control, and commitment to independence are positively associated with internal whistleblowing intentions. For external whistleblowing intentions, attitude has a positive association, desired moral approval has no significant association, and perceived behavioral control and commitment to independence have significant negative associations. Group cohesion weakens the relationship between attitude and internal whistleblowing intentions and the relationship between desired moral approval and external whistleblowing intentions but does not moderate the other relationships examined. Team norms are positively associated with group cohesion. These findings demonstrate that auditors’ internal and external reporting intentions are shaped differently and that group cohesion has a selective rather than pervasive moderating role. The study extends the theory of planned behavior and institutional theory by integrating individual, team, and institutional factors in explaining auditors’ whistleblowing intentions.